Synchronization of Storage Tank Volume, Disposal Well Volume and Electric Submersible Pump (ESP) Pump Capacity in Disposal Well Field A - Musnal, Ali; Fitrianti (UIR PRESS, 2021)
In producing oil, one of the common problems faced by oil and gas companies is the production of a lot of water. Increased water production causes the storage tank to be unable to accommodate the produced water. To overcome the excess water production, some of the water is injected back into the well. In Field A, an innovation has been made for a water injection pump with the driving force coming from the Electrical Submersible Pump (ESP) pump. The working principle of this ESP pump is to drain water from the disposal well to the injection well. Therefore, in order for the injection to run optimally, synchronization is carried out starting from the water entering the holding tank, the flow rate in the Disposal well and the pump capacity (ESP) for injecting from the holding well to the injection well. The amount of water flow rate injected through the ESP pump is 9,500 BWPD. For this reason, the capacity of the ESP pump as an injection pump is calculated. First, determine the water level in the tank to control the amount of flow that enters the reservoir well. Based on the results of the research that has been done, the water level in the holding tank to get a flow rate of 9,500 BWPD is 4.11 ft. And the results of the calculation of water will be injected using an ESP pump with a number of stages 22 with the TRW Reda Pump Devision pump type. The water will be channeled to the injection well with a type of galvanized iron pipe with a diameter of the main pipe (mainline) of 6 inches. From the disposal well, it flows with a 4 inch pipe as far as 45.93 ft and a 2 inch pipe as far as 2214.57 ft for well 07. As for wells 60, the flowline size is 4 inches as far as 708.66 ft and 2 inches as far as 987.53 ft.